Comparative analyses on nitrogen removal microbes and functional genes within anaerobic–anoxic–oxic and deoxidation ditch sewage-treating processes in Wuhan and Xi’an cities, China - Liu, Shuangyuan; Liu, Yaqi; Ye, Linyan; Xiao, Enrong; Xu, Dong; Chao, Hongjun; Dai, Jingcheng; Qiu, Dongru (Frontiers in Microbiology, 2024)
IntroductionAnaerobic–anoxic–oxic (A2/O) and deoxidation ditch (DOD) processes are being increasingly preferred owing to their effectiveness in treating various wastes in wastewater treatment plants (WWTPs). Considering seasonal variations is crucial in optimizing treatment processes, ensuring compliance with regulations, and maintaining the overall efficiency and effectiveness of WWTPs. This study aimed to determine the influence of seasonality on nitrogen removing microbes and functional genes within A2/O and DOD processes in the humid Wuhan and semi-arid Xi’an cities, China.MethodsThe physicochemical parameters of water quality were determined, and molecular and bioinformatic analyses of the bacterial community and nitrogen metabolism functional genes in the two different treatment processes of two WWTPs were performed over four seasons.Results and discussionOur analyses revealed a significant difference in all physicochemical parameters across all experimental groups (p < 0.05). At the genus level, the abundance of Dokdonella, one unidentified genus of Nitrospiraceae, Terrimonas, and one unidentified genus of Chloroflexi was the highest in all groups. Generally, warmer seasons exhibited higher biodiversity indices. The A2/O system exhibited higher values in terms of most nitrogen metabolism functional genes than those of the DOD sewage treatment system. In both WWTPs, the abundance of most genes in spring and summer were higher than that of autumn and winter seasons. Taken together, changes in temperature, caused by seasonal changes, may contribute to changes in abundance of nitrogen metabolic functional genes.